Public perceptions of road pavement conditions on Kansas Interstate 70 - Geist, Katherine H. (Kansas State University, 2019)
Poorly maintained road infrastructure is one of the most quickly growing infrastructure issues that America faces. This is due many different factors, including a lack of funding, old roads, general wear and decay, congestion, and many others. One of the biggest questions is how to combat this problem, to potentially save lives as this poor maintenance can lead to crashes, vehicle wear, etc. Another big question is whether or not citizens see this issue as a problem or not. This study involved surveying highway travelers to gauge their view on the quality of Kansas Interstate 70, to see what their opinions were on fixing this problem, and to inquire about their willingness to pay for these smoother roads. By getting to the root of the problem and speaking to those who deal with it firsthand, we will be provided with the best information that could lead to reversing it.
Keywords: Highways; Transportation planning; Survey; Stated preference